2020
DOI: 10.1002/alz.12061
|View full text |Cite
|
Sign up to set email alerts
|

A novel sensitive assay for detection of a biomarker of pericyte injury in cerebrospinal fluid

Abstract: Introduction Blood‐brain barrier (BBB) breakdown and loss of brain capillary pericytes contributes to cognitive impairment. Pericytes express platelet‐derived growth factor receptor‐β (PDGFRβ) that regulates brain angiogenesis and blood vessel stability. Elevated soluble PDGFRβ (sPDGFRβ) levels in cerebrospinal fluid (CSF) indicate pericyte injury and BBB breakdown, which is an early biomarker of human cognitive dysfunction. Methods A combination of reagents and conditions were tested, optimized, and validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 43 publications
(145 reference statements)
2
56
1
Order By: Relevance
“…Neuron-specific enolase (NSE) and GFAP are also promising biomarkers that can be detected in the CSF to identify BBB breakdown (Kadry et al, 2020 ). A study reported that the elevated level of sPDGFRβ is associated with damage to the pericytes and BBB disruption leading to a decline in cognition (Sweeney et al, 2020 ). Soluble PDGFRβ as a biomarker was also observed in VaD (Iadecola, 2017 ; Sweeney et al, 2019a ) and various other neurological diseases (Sweeney et al, 2018a , 2019b ).…”
Section: Biomarkers Associated With Bbb Breakdownmentioning
confidence: 99%
“…Neuron-specific enolase (NSE) and GFAP are also promising biomarkers that can be detected in the CSF to identify BBB breakdown (Kadry et al, 2020 ). A study reported that the elevated level of sPDGFRβ is associated with damage to the pericytes and BBB disruption leading to a decline in cognition (Sweeney et al, 2020 ). Soluble PDGFRβ as a biomarker was also observed in VaD (Iadecola, 2017 ; Sweeney et al, 2019a ) and various other neurological diseases (Sweeney et al, 2018a , 2019b ).…”
Section: Biomarkers Associated With Bbb Breakdownmentioning
confidence: 99%
“…BBB deterioration has also been observed in these same neurodegenerative conditions (10,64,65). Recently, a blood biomarker of BBB deterioration was also proposed for AD (66), and the two-hit vascular hypothesis of AD proposes the BBB disruption is an initiating event in amyloid beta deposition in the brain (54). In support of this, human studies have identified alteration in BBB permeability at the earliest stages of cognitive decline and AD (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of these pathological events could be detected using imaging approaches that indicate WMH, ischemic manifestations, subcortical hemorrhages, and microbleeds. A new sensitive assay was recently developed allowing pericyte injury detection in the CSF, a new technology that could serve as a diagnostic tool for WMD (Sweeney et al, 2020). CADASIL develops gradually over time and the earliest symptoms appear on average around 30 years of age, usually 10 years earlier in women than men, and are manifested as migraines with aura (Guey et al, 2016;Di Donato et al, 2017).…”
Section: Genetic Csvdmentioning
confidence: 99%